Sequence of Four Orthogonal Smectic Phases in an Achiral Bent-Core Liquid Crystal: Evidence for the SmAP(alpha) Phase - Vij, Jagdish; Panarin, Yuri (My University, 2011)
The mesomorphic properties of an achiral bent-core liquid crystal derived from 4-cyanoresorcinol are studied by polarizing optical microscopy, x-ray diffraction, and second harmonic electro-optic response. It shows a novel sequence of four nontilted or orthogonal smectic phases on cooling: SmA-SmAP(R)-SmAP(X)-SmAP(A). Here SmAP(X) is the new orthogonal polar uniaxial smectic phase. The electric-field-induced transformations in the SmAP(X) phase give rise to two biaxial states separated by a uniaxial one. The second harmonic electro-optic response in this phase is interpreted in terms of the polar interaction with the electric field. A comparison of the experimental results with the next-nearest-neighbor model for the structure of the SmAP(X) phase shows it to be an SmAP(alpha) phase.
PUBLISHED
Keywords: Particles and fields physics; Nanoscience & Materials